THE EFFECT OF FASHIONISTA ON FEMALE BODY IMAGE - Ismael, Bushra Jameel (ALBAHITH ALALAMI, 2020)
The research aims to reveal the relationship between the use of social networking sites and the image that females make about their physical formation, the nature of the effects, their value judgments about the image of their bodies, their attitudes toward plastic surgery, the most important types of these processes for them, their motivations to conduct them, and the cultural pressures they are exposed to. The study, moreover, investigates in the effects of those plastic surgery on their behavior as active and interacting users with what is published on social media, according to the theory of social comparison. This paper is an attempt to understand the pattern of social networking operation and its implications for the human self. The research community formed of "females", and the sample included (204) respondents from the followers of "fashionista/ fashionist". The survey approach was used over the intentional sample method to obtain research data through the electronic questionnaire. The questionnaire contained closed questions and phrases according to Likert scale. The research reached several results, including: The sample of the research mostly ranges between 18-28 years of age, having a university education, and are not married and economically sufficient. Always interested in following "fashion" from "fashionista", and sometimes learning cooking techniques, and rarely follow "fashionist". They have a desire to perform plastic surgery, and they were respectively "filler and Botox, remove wrinkles", rhinoplasty, plastic surgery and whitening teeth, sculpting the waist and buttocks, getting the lip of the duck, and finally liposuction and stomach cutting. As for their motives of plastic surgery, mostly, are done in order to satisfy themselves, and in the second place to satisfy people, and in the third position to satisfy their husbands, and in the fourth position to obtain a husband. Finally, they do that to get a job.